Characterization of excitation source LEDs and sensors without filters for measuring fluorescence in fluorescein and green leaf extract - Miguel Ángel Garrido Tamayo; Fredy Edimer Hoyos Velasco; John E. Candelo-Becerra (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This paper presents the characterization of excitation source LEDs and sensors without filters for measuring fluorescence in fluorescein and green leaf extract. For this purpose, eight light-emitting diodes (LEDs) were used with the following characteristics: one blue, one green, one red, one infrared, and four violets. The first four LEDs were used as sensors without filters to detect fluorescence induced by the other four violet LEDs in 11 samples of different fluorescein concentrations and in 14 samples of different dilutions of green leaf extract. The results show that infrared LEDs can detect the red emission of green leaf extract and red and infrared LEDs detect the fluorescence of fluorescein in concentrations of up to 1.8 μM. The developed system allows and facilitates teaching optical spectroscopy in basic education without incurring high costs.